UPAYA MENINGKATKAN KEMAMPUAN KONEKSI MELALUI PENDEKATAN CONTEXTUAL PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL DI KELAS 8C SMP NEGERI I MALEBER - Ayi Haryati (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
AbstractThe purpose of this classroom action research: 1) To obtain the aplication of contextual approach in learning mathematics to improve mathematical connection ability on  equations system liniear two variable; 2) to determine attitudes and opinions of students towards mathematics learning that uses contextual approach. The research was conducted in class VII C SMP Negeri 1 Maleber in the school yaer 2015/2016 the number of subject is 30 students through three cycles with completeness minimal criteria (CMC) 74. The result in cycle 1, the number of students who achieve mastery of at least 12 students (40%) and unsuccsessful 18 students (60%). It means that classical completemenss yet achieved only an average value of 68. In the cycle II students who achieve mastery of at least 18 students (60%) and unseuccsessful 12 students (40%), it means there is an increase in classical completeness as much as 20% compare with the cycle I. In the cycle III students achieve mastery of at least 23 students (76,67%), and which has not been achieved 7 students (13,33%). It means that there is an increase of 36,67 from the cycle I and 16,67 from the cycle II. Based on the students questionnaire response was obtained by 25 (83,34%) students  obtained a sense of fun and the responses of 20 (67%) students said that easy to understand. So contextual approach  can improve the students mathematic connection ability in class VIIIC SMP Negeri 1 Maleber on  equations system liniear two variable